(untitled) (Kinesiology, 2025)
Flexibility is the first connection between rhythmic and artistic gymnasts, but it is also motor ability that distinguishes them at the sporting level. The main goal of this research was to determine whether there was a significant difference in active and passive flexibility of the lower limbs among rhythmic and artistic gymnastics competitors. The sample of participants consisted of 18 gymnasts, out of which nine were rhythmic gymnasts and the other nine artistic gymnasts, from the junior and senior age category (13 to 18 years). In the research, the following tests were used to assess active and passive flexibility, constructed by the International Gymnastics Federation (FIG): front split with the help of the hand (FSWH), front split without hand (FSWOH), side split with the help of the hand (SSWH), side split without hand (SSWOH), back split ”penche” (BSP), back split with the help of the hand (BSWH) and forward-backward split between two blocks (FBS). In order to analyse the difference between the two groups of participants (rhythmic and artistic gymnasts) in flexibility tests Mann-Whitney U Test was used, the test for independent samples. To determine the difference between the dominant and non-dominant leg, Sign Test was used to see whether there was a statistically significant difference between the arithmetic means of the tests performed by the rhythmic and artistic gymnasts, with an error of p<.05. Results showed statistically significant difference between the rhythmic and artistic gymnasts in tests of active and passive flexibility. Differences are in the dominant leg, which was expected because each element is performed on the dominant leg. Keywords: flexibility, dynamic, inactive, preferred leg, non-preferred leg